IFPRI's research program on water resource allocation: An ex-post assessment of productivity and environmental impact - Bennet, Jeffrey W. (International Food Policy Research Institute, 2013)
IFPRI has conducted research on water issues since the 1980s, seeking to better understand how water policies and institutions can be used to ensure that there will be an adequate and equitable supply of water to meet human, economic, and environmental needs. It has done this in the context of growing demands for water arising from population and economic growth. The water research program has been organized around three major themes: global modeling of future water scenarios, river basin modeling, and water institutions.